E-030 Initial hemorrhage pattern affects utility of repeat angiography following negative initial angiogram for non-traumatic subarachnoid hemorrhage. (4th July 2012) - Alexander, M; McTaggart, R; Marks, M
Abstract : Introduction: Angiography is usually performed in the work-up of patients with spontaneous subarachnoid hemorrhage (SAH). If the angiogram is negative, the role of follow-up imaging is less clear, and this role is often influenced by the pattern of SAH encountered. Perimesencephalic subarachnoid hemorrhage (PMSAH) is usually non-aneurysmal and carries an excellent prognosis. However, non-traumatic subarachnoid hemorrhage that does not follow a PMSAH pattern is less well understood. This study was conducted to better clarify the role of imaging in both PMSAH and non-PMSAH following a negative initial angiogram. Materials and Methods: Patients with the ICD-9 discharge diagnosis of non-traumatic SAH from January 2006 through November 2011 were screened. Prospectively maintained neurointerventional procedure logs were searched for patients undergoing examination for SAH during the same period. Those patients with normal DSA results were selected. Clinical data and non-invasive imaging were also reviewed. Results: 1088 patients were discharged with the diagnosis of non-traumatic SAH during the study period. 109 had a negative initial DSA. Of those, four were excluded because they had been incorrectly coded and in fact had traumatic SAH. Five patients were excluded because the initial CT performed prior to transfer from an outside hospital was not available for review. The remaining 100 patients were 24–78 years old (mean 53.1 years). 33 (33%) had Hunt & Hess (HH) grade 1 SAH, 44 (44%) had HH grade 2, 17 (17%) had HH grade 3, 4 (4%) had HH grade 4, and 2 (2%) had HH grade 5. 16 (16%) patients had no visible SAH on CT but demonstrated SAH on lumbar puncture (Fisher grade 1 SAH). 29 (29%) patients had PMSAH, and 55 had non-PMSAH. 66 (66%) patients also had a negative CTA prior to DSA. Following the initial negative angiogram, lesions were detected on follow-up imaging in five patients (5%). Two were detected with follow-up DSA. One patient with non-PMSAH was subsequently discovered to have a 2 mm aneurysm. In addition, a dural arteriovenous fistula was identified on follow-up DSA for a patient with initial non-PMSAH. Three further lesions were identified on MRI, which were thought to be source of the SAH: a cavernous malformation, a pituitary tumor, and a spinal aneurysm. Of these three patients, only the patient with the pituitary tumor had PMSAH. Negative predictive value for all imaging types following negative DSA for non-traumatic SAH was 95%. The false negative rate of initial DSA was 7.2% for patients with non-PMSAH and 2.2% in patients with PMSAH or Fisher grade 1 SAH. The Negative predictive value of initial DSA was 93% in non-PMSAH patients for detection of all lesion types and 98% for PMSAH patients. Conclusion: In patients with non-PMSAH, repeat imaging, including repeat DSA, is indicated. Those patients with PMSAH or Fisher grade 1 SAH and negative initial DSA have a lower likelihood of finding a lesion on repeat DSA. If initial non-invasive imaging is performed with the initial DSA, repeat DSA may not be needed. Competing interests: None.